SAT0097 Assessing Significant Flares in Rheumatoid Arthritis: Validity of the Omeract Preliminary Flare Questionnaire (PFQ) in the Canadian Early Arthritis Cohort. (10th June 2014) - Bartlett, S.J.; Bingham, C.O.; Choy, E.; Boire, G.; Haraoui, B.; Lin, D.; Pope, J.E.; Thorne, C.; Hitchon, C.A.; Tin, D.; Keystone, E.C.; Bykerk, V.
Abstract : Background: Rheumatoid arthritis (RA) flares are common, poorly defined, and understudied. A new tool is needed that can precisely and reliably measure significant RA flares that may signal need for evaluation for treatment change. Qualitative and quantitative research by the OMERACT RA Flare Group with an international group of scientists, patients and healthcare providers has led to the identification of an RA Flare Core Domain Set which was ratified by OMERACT 2012 attendees. Objectives: To evaluate construct validity of the OMERACT Preliminary Flare Questionnaire in a large early RA observational trial. Methods: 501 patients in the Canadian early ArThritis CoHort (CATCH) completed PFQs at two consecutive visits from 11-2011 through 5-2013. Flare status was classified using rheumatologist and patient evaluations as well as two criteria for using DAS scores that have been proposed. Patient completed PFQs for pain, physical function (PF), fatigue, stiffness, participation and coping over previous week using 11-point NRS scales, as well as HAQ, SF12, RADAI, WPAI and Patient Global. MDs provided clinical ratings. Inter-rater reliability was assessed using % agreement and kappa. Spearman correlations were calculated between PFQs and legacy items/scales. Results: At enrollment, participants were mostly female (75%), white (83%), and 59% had > HS education. Mean (SD) age was 55 (15) years and RA duration 6 (3) months. 33% of patients were classified as being in a flare by MDs; percentage agreement across 3 other classification methods ranged from 71-74% (kappa = 0.15-0.35). Irrespective of flare definition, correlations were strongest between PFQ pain and other pain scales (r's=0.76-0.93); and moderate-strong correlations were evident among PFQ with other measures of PF (r's=0.60-0.83), fatigue (r's=0.59-0.88), stiffness (r=0.52-0.69), participation (r's=0.49-0.86) and coping (r's=0.42-0.83). Conclusions: Using 4 different flare classification systems, there was substantial association among single item PFQs and legacy RA measures. These results from a large national observation study increase confidence in the construct validity of OMERACT PFQ items to assess core domains in early RA. Additional psychometric evaluation is needed to establish the reliability, validity, and responsiveness of the PFQ and relevant thresholds across a range of RA populations and settings prior to widespread use. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3928